(untitled) (Economic and Political Thought, 2012)
The article presents the analysis of factors limiting the international competitiveness of the European universities. It calls for many reforms that should be implemented by the European universities and decisionmakers, especially in Poland. The author emphasizes that the countries with economies based on technological forms, which have effective mechanisms of knowledge, technology and innovation transfer between business and science sectors, will have best prospects in the new global economic reality. This is where, i.e. the sector of scientific research and higher education, Polish elites should look for new, effective mechanisms of development and strengthen them just now as any changes in the sector of higher education and research require relatively long time (at least 4 years) to produce results.